The corporate brand - Ind, Nicholas (New York University Press, 1997)
Regardless of the service or products it provides, a company's corporate brand is responsible for its image and reputation in the minds of its products' consumers. And yet companies rarely focus on what leads to a successful corporate brand, concentrating their energy instead on their individual brand name products. In The Corporate Brand, Nicholas Ind argues strongly for a new focus on corporate brand development. The Corporate Brand shows how organizations can best manage their reputations. Nicholas Ind argues that organizations must use all forms of communication, including performance of specific products, employees' services, and advertising, to build effective interactive relationships with their customers. The Corporate Brand elucidates the methods used by successful corporate brands to build and maintain both "corporate identity" and reputation.